Factors Influencing Modern Family Planning Utilization and Barriers in Women of Reproductive Age in the Iringa Region, Tanzania: A Mixed-Methods Study - Besha E. Ngole MSc; Angelina A. Joho PhD (SAGE Open Nursing)
Background Preventing unwanted pregnancies, achieving optimal child spacing, and improving quality of life are benefits of modern family planning (FP). This study aimed to assess modern FP use, identify the factors influencing its use and determine the barriers to FP use among women of reproductive age. Methods A mixed-methods approach was conducted in the Iringa Region between March and July 2022. Conveniently, 368 women of reproductive age were included in the quantitative study, and 48 were purposively selected for the qualitative study based on reported barriers to using modern FP. Interviewer-administered questionnaires and interview guides were used for data collection. The factors of modern FP use were determined using multivariable logistic regression analysis. The p  < 0.05 was considered to be significant. For qualitative data, all interviews were recorded and transcribed. Data were analyzed manually through thematic analysis. Results The prevalence of modern FP use was 181 (49%). Being married (adjusted odds ratio [AOR] = 5.44, 95% confidence interval [CI] = 1.77–16.73, p  = .003), parity of 6 and more (AOR = 2.43, 95% CI = 1.99–5.95, p  = .052), availability of modern FP methods (AOR = 1.71, 95% CI = 1.03–2.85, p  = .038), and women with primary education level (AOR = 2.99, 95% CI = 1.03–3.25, p  = .001), women with secondary and higher education (AOR = 3.53, 95% CI = 1.41–4.38, p  = .001), were predictors for modern FP utilization. Four main themes merged (1) individual barriers, (2) hospital barriers, (3) cultural barriers, and (4) knowledge of modern FP methods. Conclusion The use of modern FP increases with women's education. There is a need for the government to invest in women's education and raise awareness and knowledge of the benefits of modern FP methods.